Obeah, Orisa, and Religious Identity in Trinidad, Volume I, Obeah Africans in the White Colonial Imagination, Volume 1 - Hucks, Tracey E. (Religious Cultures of African and African Diaspora People, 2022)
Tracey E. Hucks traces the history of the repression of Obeah practitioners in colonial Trinidad.